PERCEPTION OF PHYSICAL EDUCATION STUDENTS ON THE INFRASTRUCTURE OF BIG BALL SPORTS - Nikmatin, Dwi Laily Septi; Apriliyanto, Rizki; Sulaiman, Ahmad (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
The purpose of this study was to determine the perception of physical education students of the University of muhammadiyah jember class of 2021 on the feasibility of infrastructure for large ball sports, namely football, volleyball and basketball. The research method used is a quantitative descriptive method, the population in this study is all physical education students of the 2021 batch, the sample taken using a total sampling of 21 students. With data collection techniques using kuesioner closed through google form. The questions in kuesioner cover the facilities and infrastructure of big ball sports (football, volleyball, and basketball). The data obtained will be analyzed using descriptive statistical methods in which data analysis includes calculating the frequency, average, and percentage. Based on research that has been conducted 81,55% of respondents considered that the facilities and infrastructure in the Football course in the category of decent, 76,49% of respondents considered that the facilities and infrastructure in the volleyball course in the category of decent, and 77,08% of respondents considered that the facilities and infrastructure in the basketball course in the category decent.